Diagnostic Accuracy of C-Reactive Protein and Erythrocyte Sedimentation Rate in Patients with Acute Scrotum - Asgari, Seyyed Alaeddin; Mokhtari, Gholamreza; Falahatkar, Siavash; Mansour-Ghanaei, Mandana; Roshani, Ali; Zare, Alireza; Zamani, Mehrangiz; Khosropanah, Iradj; Salehi, Mohammad (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: Our aim was to investigate the diagnostic accuracy of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) in patients with acute scrotum. Materials and Methods: One hundred and twenty patients with acute scrotum were evaluated and divided into 3 groups: 46 with acute epididymitis (group 1), 23 with spermatic cord torsion (group 2), and 51 with other noninflammatory causes of acute scrotum (group 3). Serum levels CRP and ESR were measured at the time of admission. Results: Of the patients in group 1, 44 (95.6%) had elevated serum levels of CRP (mean, 67.77 ± 47.80 mg/L). In contrast, only 1 patient in group 2 had a significant increase in the serum level of CRP (mean, 9.0 ± 4.90 mg/L), and the patients in group 3 did not have any significant increase in the CRP levels (mean, 7.0 ± 2.2 mg/L) (P < .001). The mean ESR values were 45.9 ± 21.4 mm/h, 14.2 ± 11.2 mm/h, and 8.8 ± 7.5 mm/h, in groups 1 to 3, respectively (P < .001). The cutoff points for distinguishing between epididymitis and noninflammatory causes of acute scrotum were 24 mg/L for CRP and 15.5 mm/h for ESR. The sensitivity and specificity values were 93.4% and 100% for CRP and 95.6% and 85.1% for ESR, respectively. Conclusion: Based on our findings, serum levels of CRP and ESR can provide helpful information for differentiation between epididymitis and other causes of acute scrotum. We recommend CRP and ESR measurements before making a decision of surgical intervention.